Effects of Seed Rate and Harvesting Stage on Nutrient Composition and the Dry Matter Yield of Setaria pumila Grass Under Rain-Fed Conditions in Debre Markos, Ethiopia - Aynalem Binalf; Shashie Ayele; Zewdu Wondifraw (Advances in Agriculture)
The low productivity of livestock in Ethiopia seems to originate from the poor quality and quantity of feed. One of the options to solve the problem of food scarcity and increase livestock productivity could be to select and evaluate the naturally available grass species in natural pasture grasslands and introduce them into different forage production strategies, Thus, the current study aimed at to examine the yield and nutrition content of Setaria pumila grass at three stages of harvest and seed rates (SRs). A factorial treatment arrangement of randomized complete block design (RCBD) having 3 × 3 factors replicated into three on a 2 × 3 m2 plot size was used. The first factor was the harvest stage (HS), which had three levels, such as 50% heading stage (HS1), full flowering stage (HS2), and 30 days delayed after a full flowering stage (HS3). The second factor was the SR, which was seeded at 2 kg/ha (SR1), 3 kg/ha (SR2), and 4 kg/ha (SR3). PROC GLM of SAS software was used for data analysis. The results showed that height of the plant (PH) (58.7–106.8 cm), tiller number per plant (TNPP) (31–39), leaf number per plant (LNPP) (130–163), leaf area (LA) (13.7–21 cm2), and dry matter yield (DMY) (5.6–11.7 tons/ha) increased with increasing HS in order of HS1 < HS2 < HS3 (p<0.0001). Similarly, neutral detergent fiber (NDF) (65.6%–75.7%) and acid detergent fiber (ADF) (34.5%–43.6%) increased as the plant stage moved from HS1 to HS3, while leaf-to-stem ratio (LSR) (1.8–0.6) and crude protein (CP) (9.75%–5.89%) declined as the plant stage advanced. The current result also showed that as the SR went up from SR1 to SR3, the measurements for PH (76.9–87 cm), LA (15.8–18.8 cm2), DMY (8–9 tons/ha), NDF (69%–73%), and ADF (36%–41%) increased, while the values for TNPP (44–27) and LNPP (221–83) decreased as the SR increased. However, the effect of SR on LSR, ash, and CP contents was not apparent (p>0.05). Therefore, it was concluded that Setaria pumila grass should be seeded at an amount of 4 kg/ha and harvested just in the full flowering stage (HS2) to obtain a high yield with a better nutrient content. Integrating Setaria pumila grass with herbaceous leguminous forage species to optimize its quality and yield should be further investigated.